2017
DOI: 10.3390/educsci7020052
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Instructional Guidance and Sequencing of Manipulatives and Written Symbols on Second Graders’ Numeration Knowledge

Abstract: Concrete objects used to illustrate mathematical ideas are commonly known as manipulatives. Manipulatives are ubiquitous in North American elementary classrooms in the early years, and although they can be beneficial, they do not guarantee learning. In the present study, the authors examined two factors hypothesized to impact second-graders' learning of place value and regrouping with manipulatives: (a) the sequencing of concrete (base-ten blocks) and abstract (written symbols) representations of the standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…In this sense, it may be helping to slow children down just enough to promote more reflection and engagement with the problem, setting the stage for deeper conceptual learning. Similar explanations may help to explain previously reported phenomena in the field of mathematics education, such as work showing that second grade children learned more about place value when instruction was provided first on symbolic numerals then on concrete manipulatives rather than the other way around (Osana et al 2017).…”
Section: Discussionsupporting
confidence: 58%
“…In this sense, it may be helping to slow children down just enough to promote more reflection and engagement with the problem, setting the stage for deeper conceptual learning. Similar explanations may help to explain previously reported phenomena in the field of mathematics education, such as work showing that second grade children learned more about place value when instruction was provided first on symbolic numerals then on concrete manipulatives rather than the other way around (Osana et al 2017).…”
Section: Discussionsupporting
confidence: 58%
“…External representation as concrete objects could be used to illustrate and manipulate symbolic numbers. Some studies (e.g., Osana, Adrien, & Duponsel, 2017) tested such methods in TD children and showed that children benefit from an instruction starting with manipulatives and pursuing with symbolic numbers in understanding of place-value concept and addition algorithm for example. However, it remains unclear if they would be helping for children with MLD, so that future studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Because they need instructional support to base their comparisons on structural similarities (Richland et al, 2007;Vendetti et al, 2015), it stands to reason that the more physically similar the two systems are, the greater the likelihood they will abstract the common conceptual structure between them. With respect to manipulatives specifically, proportional manipulatives-those that made the relative sizes of the denominations transparent-were more beneficial for children's transfer of place-value concepts than objects that relied on color alone to distinguish the size of the denominations (Osana et al, 2018).…”
Section: Using Manipulatives In Mathematicsmentioning
confidence: 99%